An Analysis Student’s Intonation in Reading English Newspaper - Rabiatul Adawiyah; Barus, Siti Khadijah; Emeliya Sukma Dara Damanik (Universitas Pendidikan Ganesha, 2023)
Intonation learning is necessary for everybody in variety of purposes and needs. Students still have difficulties in pronouncing the words with right intonation. They were still shy to pronounce the words in English well. They were afraid their friends will laugh them when they pronounce the words. This research come from the research with the aim is to analyze students’ intonation ability by reading a paragraph and to find the difficulties students’ intonation. The subject of this study is third grade English education department by reading a paragraph in newspaper. This study uses a descriptive qualitative method. The data collection method was taken from test and it was recorded. The result was found that students’ rising intonation by reading a paragraph of the third grade English education department was still low score 56.5. The students got difficult in rising intonation and the dominantly wrong when intonated the text. It is concluded that students’ rising intonation by reading a paragraph students of the Third Grade English Education Department was still low.